Validation study on the assay method for anti-factor IIa potency of enoxaparin sodium - Yang, Xiaorong; Zou, Hanyan; Dong, Yixue; Liu, Bing; Wang, Ying; Wang, Mengying (PeerJ, 2024)
Enoxaparin sodium is a low molecular mass heparin essential for effective anticoagulation therapy. However, significant variations in testing methods across different manufacturers have led to poor reproducibility of results, increasing the risks associated with drug quality evaluation by manufacturers and regulatory oversight. This study integrates the strengths of various testing methods to establish a reproducible assay that has been thoroughly validated. The validation results demonstrate that the method exhibits excellent specificity, linearity, robustness, precision, and accuracy, with recovery rates ranging from 98.0% to 102.0%. The new method demonstrated high consistency and reproducibility, with an RSD value of less than 2.0%, and showed the potential to replace the European Pharmacopoeia method by reducing reagent usage, experimental costs, and equipment requirements. The reliable results of this method facilitate its adoption across different laboratories, enhance the quality control of enoxaparin sodium, and provide a reference for new manufacturers and drug regulatory authorities, thereby ensuring medication safety.
Keywords: Enoxaparin sodium; Potency assay; Method validation; Pharmaceutical quality control; Anti-factor IIa